Preliminary Study on the Influence of Potting Soil on Magnolia grandiflora L. Seed Germination and Plant Growth - Daniela Sabina POȘTA; Giancarla VELICEVICI; Ioana Mihaela MĂLĂESCU; Marius SILIVĂȘAN; Veronica SĂRĂȚEANU; Tincuța-Marta GOCAN; Orsolya BORSAI; Sandor RÓZSA; Ilie-Cosmin CÂNTAR; Roberto Renato BERNARDIS (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Horticulture)
Magnolia grandiflora L. it is known mostly for its ornamental values, but it has a significant medicinal value as well through its flowers, which have a great antioxidant activity. The main aim of this study was to investigate the influence of potting soils on seed germination and plant development. The seeds were removed from the fruits and stored at constant humidity of (80%) and temperature (4 °C) for 90 days. The seeds were then sown in different potting soils: V1 - Potgrond H peat; V2 – Zelta Zeme peat; V3 – Kekkilä peat; V4 – TS 3 peat. After germination, the germination percentage and seed vigour index were determined. The plantlets were further monitored and after 60 days of growth several traits were determined: seedling height, girth diameter, root number, primary root length, leaf number, leaf length, leaf width, leaf shape index, average leaf area and total leaf area. The maximum germination percentage was reached in Potgrond H peat (100%), followed by Zelta peat (90%) in 8 and 10 days respectively. Regarding seedling development, the results revealed that V3 - Kekkilä peat stimulated the most plant growth and development, exhibiting the highest values for all parameters measured, both for underground and above ground parts of the plant.